Carbohydrate supplementation and the lymphocyte proliferative response to long endurance running - Henson, D. A.; Nieman, D. C.; Parker, J. C.; Rainwater, M. K.; Butterworth, D. E.; Warren, B. J.; Utter, A.; Davis, J. M.; Fagoaga, O. R.; Nehlsen-Cannarella, S. L. (International Journal of Sports Medicine, 1999)
This randomized, double-blind, placebo-controlled study examined the influence of 6% carbohydrate ingestion on hormonal and lymphocyte proliferative responses (5 total samples over 9 hours) to 2.5 h of high-intensity running by 30 experienced marathon runners. The T-cell response differed between groups, with the placebo group exhibiting a greater increase immediately post-run and greater decrease at 3 h of recovery. No group differences were observed for Con A-, PHA-, or PWM-induced lymphocyte proliferation. However, when PHA was adjusted per T-cell, group differences were observed, highlighted by a decrease in the placebo group immediately post-run. Glucose and cortisol responses differed between groups, with glucose lower and cortisol higher in the placebo group immediately post-run. Post-run glucose correlated negatively with postrun cortisol (r=-0.670, P< 0.001) and epinephrine (r=-0.540, P=0.002). Post-run cortisol also correlated negatively with total lymphocytes and T-cells at 1.5 hours (r=-0.429, P=0.018 and r=-0.424, P=0.019, respectively) and 3 hours (r=-0.566, P=0.001 and r=-0.523, P=0.003, respectively) of recovery. The pre- to post-run change in glucose correlated to the same changes in PHA/T-cell (r=0.456, P=0.011). The data support an interactive effect of carbohydrate ingestion on plasma glucose and cortisol. The data support an interactive effect of carbohydrate ingestion on plasma glucose and cortisol, T-cell trafficking, and cell-adjusted PHA-induced lymphocyte proliferation following long endurance running.